KOTA SURABAYA MENUJU SMART CITY - , Dwita Widyaningsih; , Prof. Ir. Achmad Djunaedi, MUP., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Smart City is one of new strategies city development and city management. This concept emerged and evolved coincided with changing times and technology. Smart City is defined as âa city to be smart when investments in human and social capital and traditional and modern communications infrastructure fuel sustainable economic growth and a high quality of life, with a wise management of natural resources, through participatory governanceâ (Nijkamp, et al in Chaffers, 2010:3). Since this concept is still new, the study related to this concept still being conducted. Surabaya is the city that won the Smart City Award 2011, held by Warta Ekonomi magazine. Considering that in the world Smart City concept is still evolving, but Surabaya City was already winner in Smart City Awards 2011 become interesting to study. Previous studies about Smart City described dominantly components, character, dimensions, factors, and strategies of Smart City, but those studies were lack to explaine the process of urban development towards the Smart City. Therefore the aim of this study is to describe how the process the City of Surabaya towards Smart City and explore the process at its development. The study approach used a qualitative approach with a exploratory case study method. The results of this study were that the development process towards the Surabaya City Smart City is not sectoral, but rather a holistic approach. There were 4 phases: the phase of internal government reform, the phase of strengthening of social capital, the phase of development of external government service, and the phase of the development of high technology-based city service.